Genetic Variability, Correlation and Path Analysis in Ridge Gourd [Luffa acutangula (Roxb.) L.] - B Varalakshmi (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2015)
The present investigation was made to determine variability, heritability, genetic advance and correlation of fruit yield with 10 yield-contributing traits in ridge gourd. A wide variability was observed for days taken to first female flower appearance, fruit length, fruit number/plant, fruit weight and fruit yield/ha. Phenotypic coefficient of variation was higher than genotypic coefficient of variation for all the traits studied, indicating environmental influence on the expression of these traits. However, high heritability (broad-sense), along with high genetic advance, was recorded in node number at which first female-flower appeared, number of branches, fruit length, number of fruits/plant and fruit weight, indicating presence of additive gene effects. Fruit yield/ha was significantly and positively associated with peduncle length, fruit length, number of fruits/plant (at the phenotypic level), fruit weight and fruit yield/plant. Fruit weight had the highest direct effect (0.847) on fruit yield/ha, followed by fruit yield/plant (0.793), fruit number (0.344), peduncle length (0.237) and number of branches (0.216). Therefore, for yield improvement in ridge gourd, emphasis may be laid on indirect selection using fruit parameters like fruit weight, number of fruits/plant and fruit yield/plant.